THE TRANSFER OF RESPONDENT ELICITING AND EXTINCTION FUNCTIONS THROUGH STIMULUS EQUIVALENCE CLASSES - Dougher, Michael J.; Augustson, Erik; Markham, Michael R.; Greenway, David E.; Wulfert, Edelgard (Journal of the experimental analysis of behavior, 1994)
Two studies investigated the transfer of respondent elicitation through equivalence classes. In Experiment 1, match‐to‐sample procedures were used to teach 8 subjects two four‐member equivalence classes. One member of one class was then paired with electric shock, and one member of the other class was presented without shock. All remaining stimuli were then presented. Using skin conductance as the measure of conditioning, transfer of conditioning was demonstrated in 6 of the 8 subjects. In Experiment 2, similar procedures were used to replicate the results of Experiment 1 and investigate the transfer of extinction. Following equivalence training and conditioning to all members of one class, one member was then presented in extinction. When the remaining stimuli from this class were then presented, they failed to elicit skin conductance. In the final phase of the experiment, the stimulus that was previously presented in extinction was reconditioned. Test trials with other members of the class revealed that they regained elicitation function. These results demonstrate that both respondent elicitation and extinction can transfer through stimulus classes. The clinical and applied significance of the results is discussed.